Attitudes of Male and Female Teachers towards Inclusion of Students with Intellectual Disability in Regular Schools in the State of Kuwait - Fayez Aldhafeeri (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to identify the attitudes of male and female teachers towards inclusion of students with intellectual disability in mainstream schools in the State of Kuwait. This study was applied on male and female teachers from regular middle schools in the first semester of (2019 - 2020) school year. The sample was (233) male and female teachers; (135) male teachers and (98) female teachers were intentionally selected. They were asked to answer a 20-item scale prepared by the researchers. Then, the researchers conducted semi-structured interviews with (18) male and female teachers. The results revealed that the level of male and female teachers' attitudes toward inclusion was moderate. In addition, the results revealed that six proposals contribute in enhancing male and female teachers attitudes toward inclusion of students with intellectual disability as follows: (1) providing employees of Ministry of Education with an action plan about how to perform inclusion process; (2) training male and female teachers; (3) providing university students with a course about inclusion of students with intellectual disability; (4) reducing the number of students in the classroom; (5) providing appropriate curricula for all students; and (6) educating the community.